Comparison of spatially matched airways reveals thinner airway walls in COPD. The Multi-Ethnic Study of Atherosclerosis (MESA) COPD Study and the Subpopulations and Intermediate Outcomes in COPD Study (SPIROMICS). Issue 11 (13th June 2014) - Smith, Benjamin M; Hoffman, Eric A; Rabinowitz, Dan; Bleecker, Eugene; Christenson, Stephanie; Couper, David; Donohue, Kathleen M; Han, Meilan K; Hansel, Nadia N; Kanner, Richard E; Kleerup, Eric; Rennard, Stephen; et al.
Abstract : Background: COPD is characterised by reduced airway lumen dimensions and fewer peripheral airways. Most studies of airway properties sample airways based upon lumen dimension or at random, which may bias comparisons given reduced airway lumen dimensions and number in COPD. We sought to compare central airway wall dimensions on CT in COPD and controls using spatially matched airways, thereby avoiding selection bias of airways in the lung. Methods: The Multi-Ethnic Study of Atherosclerosis (MESA) COPD Study and Subpopulations and Intermediate Outcomes in COPD Study (SPIROMICS) recruited smokers with COPD and controls aged 50–79 years and 40–80 years, respectively. COPD was defined by current guidelines. Using CT image data, airway dimensions were measured for all central airway segments (generations 0–6) following 5 standardised paths into the lungs. Case-control airway comparisons were spatially matched by generation and adjusted for demographics, body size, smoking, CT dose, per cent emphysema, airway length and lung volume. Results: Among 311 MESA COPD participants, airway wall areas at generations 3–6 were smaller in COPD compared with controls (all p<0.001). Among 1248 SPIROMICS participants, airway wall areas at generations 1–6 were smaller (all p<0.001), and this reduction was monotonic with increasing COPD severity (p<0.001). In both studies, sampling airways by lumen diameter or randomly resulted in a comparison of more proximal airways in COPD to more peripheral airways in controls (p<0.001) resulting in the appearance of thicker walls in COPD (p<0.02). Conclusions: Airway walls are thinner in COPD when comparing spatially matched central airways. Other approaches to airway sampling result in comparisons of more proximal to more distal airways and potentially biased assessment of airway properties in COPD.